Yoga Prana Vidya healing for forehead injury and behavioral stabilization in a 26-year-old woman with congenital hearing and speech impairment: a case report - Chandreshekar, Shalini; Nanjunda Rao , Raghu (International Surgery Journal, 2025)
Individuals born with special needs may have difficulty following social rules, problem-solving, and may display frustration, aggression, self-injurious behavior, or repetitive actions. This case highlights the effective use of Yoga Prana Vidya (YPV) healing in managing a forehead injury and associated behavioral issues where conventional medicine had limited impact. A 26-year-old woman with congenital hearing and speech impairment removed her surgical stitches and refused medication. Daily distant YPV healing—level 3 for emotional stabilization and level 2 for wound healing—was applied for six weeks. Significant improvements were observed, including complete wound healing, reduction of aggressive behavior, and increased cooperation in home care. This case highlights the potential of YPV as an effective complementary modality for wound healing and behavioral stabilization, particularly in individuals with special needs who may have difficulty following conventional medical procedures.